2021
DOI: 10.4037/ajcc2021854
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Chaplains’ Code Blue Responses

Abstract: Background Family presence during resuscitation is the compassionate practice of allowing a patient’s family to witness treatment for cardiac or respiratory arrest (code blue event) when appropriate. Offering family presence during resuscitation as an interprofessional practice is consistent with patient- and family-centered care. In many institutions, the role of family facilitator is not formalized and may be performed by various staff members. At the large academic institution of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Our team reviewed the baseline prevalence and management of FPDR within the institution. In our review of chaplain code blue documentation from the years 2012 to 2019, we found that family were present at just over 50% of inpatient code blue events documented by chaplains, 29 which confirmed the incidence of FPDR and emphasized the broad scope of the chaplain during resuscitation events. These data were shared throughout the institution and supported the relevance of the pathway development.…”
Section: Processmentioning
confidence: 52%
See 4 more Smart Citations
“…Our team reviewed the baseline prevalence and management of FPDR within the institution. In our review of chaplain code blue documentation from the years 2012 to 2019, we found that family were present at just over 50% of inpatient code blue events documented by chaplains, 29 which confirmed the incidence of FPDR and emphasized the broad scope of the chaplain during resuscitation events. These data were shared throughout the institution and supported the relevance of the pathway development.…”
Section: Processmentioning
confidence: 52%
“…Chaplains documented family presence in 39% of code blue events from May 2021 to May 2022 compared with an average frequency of 53% in the 9 years before that. 29 Visitor restrictions related to Coronavirus may have influenced this frequency. This finding suggests that the pathway did not increase the occurrence of FPDR at this institution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations